Improving Teacher Job Satisfaction Through Competence And Compensation of Elementary Teachers - Freddrick Putra (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
Competence and compensation on teacher job satisfaction is a classic problem that is still interesting to always be used as study material for research because it is still easy to find in everyday life. This study has the aim of finding research gaps with previous research on teacher job satisfaction through competence and teacher compensation, using the following 3 research questions, how does competency influence teacher job satisfaction, secondly how does compensation affect teacher job satisfaction and thirdly how does competence and compensation influence teacher together. This method uses a quantitative approach with a total of 44 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data obtained was subjected to the classical assumption test which aims to analyze the normality of the data, the linearity of the data before entering the data analysis section using multiple linear regression. The results of the study show that partially and simultaneously competence and compensation have a positive and significant effect. The interesting finding that becomes the novelty of this research is that competence gets a more dominant value when compared to compensation.